Community Understanding of Sakinah Families Through Family Counseling - Adha, Idyana; Firman, Firman; Netrawati, Netrawati (Universitas Trunojoyo Madura, 2025)
A sakinah family is a family that is fostered by a legal marriage, able to give love to family members so that they have a sense of security, peace, peace and happiness. This study aims to determine the community's understanding of the sakinah family and the efforts made by the community in realizing the sakinah family. The research method used is qualitative with the type of descriptive research. This research was conducted for two months. The subjects in this study were five families in Korong Lubuk Punggai, Patamuan District, Padang Pariaman Regency. The research instrument is the researcher himself. Sources of data in this study are primary and secondary data sources. Data collection technique in this research is interview. From the results of research conducted in Korong Lubuk Punggai, Patamuan District, Padang Pariaman Regency, it was found that the community's understanding was quite good, meaning that most of the people understood the nature of the sakinah family, only a small portion of the community did not understand the nature of the sakinah family. An understanding of the sakinah family is a family that provides comfort, in which there are religious values, peace, having love for one another, and caring for the family. and has begun to be able to strive for the realization of a sakinah family by choosing the best and faithful partner, being open to each other in a family, good communication, solving problems together, equipping themselves with knowledge and religious values, and carrying out their respective obligations for the community. family members.